Big as life : an American history of 8mm films - Museum of Moderm Art (San Francisco Cinematheque, 1998)
Includes bibliographical references (p. 118-119); Introduction; The zapruder film; the qualities of eight; atomic cinema; I came into an 8mm world; film, kitch's last meal; baby;